A Study of Ecranisation in the Novel Invalidite: The Bridge of Perfection into Film - Irawan, Dedi; Kuswara; Prisilia, Arla Aelani (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Films adapted from novels often receive negative responses from both readers and viewers, stemming from disappointment when the film's narrative is perceived as not aligning with the original novel. Therefore, this study aims to describe the forms of ecranisation from the novel Invalidite: The Bridge of Perfection into the film Invalidite, and to describe public responses to films undergoing the ecranisation process. The method used in this research is descriptive. Data collection techniques in this study include content analysis, documentary techniques, and questionnaires. The instruments used in this research are data tables of narrative elements in the novel and film, as well as questionnaires. After analyzing the data, the results show that the study of ecranisation forms from Faradita's novel Invalidite: The Bridge of Perfection into Herwin Novianto's film Invalidite consists of forms of reduction, addition, and varied changes in plot, characters, setting, costumes, props, and accompanying music. Specifically, 51 instances of reduction, 25 instances of addition, and 38 instances of varied changes were found. This aligns with respondents' feedback, which states that films undergoing the ecranisation process inevitably experience changes. This research is expected to provide understanding and awareness to both readers and viewers to accept the changes that occur in film adaptations.